Risk Factors for Infection and Health Impacts of the Coronavirus Disease 2019 (COVID-19) Pandemic in People With Autoimmune Diseases. (6th May 2021) - Fitzgerald, Kathryn C; Mecoli, Christopher A; Douglas, Morgan; Harris, Samantha; Aravidis, Berna; Albayda, Jemima; Sotirchos, Elias S; Hoke, Ahmet; Orbai, Ana-Maria; Petri, Michelle; Christopher-Stine, Lisa; Baer, Alan N; et al.
Abstract: Background: People with autoimmune or inflammatory conditions taking immunomodulatory/suppressive medications may have higher risk of novel coronavirus disease 2019 (COVID-19). Chronic disease care has also changed for many patients, with uncertain downstream consequences. Methods: We included participants with autoimmune or inflammatory conditions followed by specialists at Johns Hopkins. Participants completed periodic surveys querying comorbidities, disease-modifying medications, exposures, COVID-19 testing and outcomes, social behaviors, and disruptions to healthcare. We assessed whether COVID-19 risk is higher among those on immunomodulating or suppressive agents and characterized pandemic-associated changes to care and mental health. Results: In total, 265 (5.6%) developed COVID-19 over 9 months of follow-up (April–December 2020). Patient characteristics (age, race, comorbidity, medications) were associated with differences in social distancing behaviors during the pandemic. Glucocorticoid exposure was associated with higher odds of COVID-19 in models incorporating behavior and other potential confounders (odds ratio [OR]: 1.43; 95% confidence interval [CI]: 1.08, 1.89). Other medication classes were not associated with COVID-19 risk. Diabetes (OR: 1.72; 95% CI: 1.08, 2.73), cardiovascular disease (OR: 1.68; 95% CI: 1.24, 2.28), and kidney disease (OR: 1.76; 95% CI: 1.04, 2.97) were associated with higher odds of COVID-19. Of the 2156 reporting pre-pandemic utilization of infusion, mental health or rehabilitative services, 975 (45.2%) reported disruptions therein, which disproportionately affected individuals experiencing changes to employment or income. Conclusions: Glucocorticoid exposure may increase risk of COVID-19 in people with autoimmune or inflammatory conditions. Disruption to healthcare and related services was common. Those with pandemic-related reduced income may be most vulnerable to care disruptions. Abstract : A large study of people with autoimmune or inflammatory conditions finds that glucocorticoid exposure may increase risk of coronavirus disease 2019 (COVID-19). The study also suggests that in this population, those with pandemic-related reduced income or employment were most vulnerable to care disruptions.